Bioinformatics and Molecular Characterization Study of the HSP60 Gene of Pomacea canaliculata (Lamarck, 1822) - Sarmad Awad Mozan AL-Asadi; Noor J. A. Jouda; Sahar M. A. AL-Mothafer; Muhammed J. Al-Emara; Ali AL-Ali (مجلة ديالى للعلوم الزراعية)
A freshwater Pomacea canaliculata snail is widely spread across countries, including Iraq, and has the possibility for habitat alterations and lives under unusual conditions. This snail has not acquired any importance in Iraq at the molecular characterization level. Therefore, the study aimed to characterize the HSP60-coding gene in P. canaliculata at bioinformatics and molecular levels and determine whether HSP60 could be used as a taxonomical marker. P. canaliculata samples were collected from the Shatt Al-Arab River, Basrah province, and cDNA was synthesized from extracted RNA. HSP60 primers were designed to amplify 1322 bases using PCR. Purified products were randomly selected for sequencing. The bioinformatics analysis showed that the HSP60 gene (12 introns and 13 exons) belonged to the nuclear genome and its protein was located in mitochondria due to having the mitochondrial transit peptide. HSP60 protein could also form high molecular weight conformational changes during catalytic cycles. The results also displayed that the HSP60 sequences from Basrah shared 100% identity. For the first time, the evolutionary network revealed four P. canaliculate genotypes and the A genotype (this study's samples) was unique compared with three different genotypes from China (B, C, and D). Likewise, the protein of the A genotype was also distinctive from Chinese proteins. These results suggest that there was only one genotype of P. canaliculate in Basrah based on the HSP60 gene/protein. HSP60 could be utilized as a taxonomical marker in studying the intraspecies in P. canaliculate and this could be applied to other gastropods.